Case report: Clinical and pathological findings in a canine patient with intervertebral disk extrusion resembling progressive myelomalacia - Lin, Annie; Lampe, Rachel; Bandt, Carsten; Vieson, Miranda; Park, Jae Yoon (Frontiers in Veterinary Science, 2023)
A 4 year old, female spayed dog presented to the emergency department for non-ambulatory tetraparesis which progressed to tetraplegia. Computed tomography (CT) confirmed cervical intervertebral disc extrusion at C5-6 extending to C6-7, and an emergency ventral slot was performed. After the procedure, the patient was placed on mechanical ventilation due to respiratory failure. Repeat assessment upon weaning her ventilatory support suggested the patient’s neurological status had declined. Based on her deterioration and suspicion of myelomalacia on magnetic resonance imaging (MRI), she was euthanized. Post mortem histopathology of the spinal cord confirmed the presence of ascending/descending myelomalacia. To the author’s knowledge this is the first case report describing an ascending myelomalacia in a canine patient with cervical intervertebral disc extrusion.